Does a Chief Executive Officer (CEO) struggle to implement effective decisions when succeeding a celebrity CEO and if so, why? - Ogunleye, David (2018)
Focusing on the succession context of replacing a celebrity CEO, this study specifically investigates whether successor CEOs struggle to enact the necessary changes to elicit positive organisational performance when replacing a celebrity CEO and the potential reasons that can inhibit their success. As a recent literature, this phenomenon has been overlooked, specifically from a qualitative perspective. This study addresses this issue by utilising a case study to provide deeper insight into the implications of succeeding a celebrity CEO. Our findings reveal that power and politics are indispensable traits for a successor CEO of a celebrity to have in order to overcome the external and internal difficulties that can encompass quotidian organisational affairs. Without an adept use of these traits, the successor’s impotence is inevitable. Furthermore, the implications of these findings for organizational succession practices are delineated.